2022
DOI: 10.3390/nano12121951
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Cure, Hardness, Roughness and Filler Dimension of Bulk-Fill Flowable, Conventional Flowable and High-Strength Universal Injectable Composites: An In Vitro Study

Abstract: (1) Objective: To evaluate and compare the depth of cure (DOC) of two bulk-fill flowable composites (Filtek Bulk Fill Flowable Restorative and Tetric EvoFlow Bulk Fill), two conventional flowable composites (Filtek Supreme XTE Flowable Restorative and G-ænial Flo X) and one high-strength universal injectable composite (G-ænial Universal Injectable). (2) Methods: specimens were placed in a stainless-steel mold with an orifice of 4 mm in diameter and 10 mm in depth and light-cured for 20 s using a light emitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…All BBH specimens cured to a depth of 8 mm (depth of cure >4 mm). The depth of cure of the bulk-fill resin-based composite base materials is reported to be considerably larger than that of conventional resin-based composites [36][37][38]. Therefore, the very large depth of cure of BBH obtained in this study is consistent with previous reports [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…All BBH specimens cured to a depth of 8 mm (depth of cure >4 mm). The depth of cure of the bulk-fill resin-based composite base materials is reported to be considerably larger than that of conventional resin-based composites [36][37][38]. Therefore, the very large depth of cure of BBH obtained in this study is consistent with previous reports [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…All flowable tested materials were marketed as a highstrength injectable restorative composite with Genial Universal FLO having a 69% by-weight filler loading of ultra-fine Strontium particles and Gaenial universal injectable as well having a 69% by-weight filler loading of ultra-fine barium particles [27]. Despite the similar filler loading, the two materials are showing different mechanical and physical performances in the current study.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Beautifil Injectable was filled with 64% by weight and Beautifil flow plus filled with 60% by weight filler loading, both fillers are based on aluminofluoroborosilicate glass and Al 2 O 3 . The difference in the filler type and weight percent used in tested materials may explain the difference between the behavior of these materials, as each filler material has different mechanical and physical properties and may influence material behavior differently [27]. This is in addition to the Surface hardness is a crucial characteristic that indicates a material's resistance to plastic deformation and abrasion [24,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in physical and mechanical properties and an increase in cytotoxicity to the dental pulp cell can occur when the material receives inadequate light penetration. 37 It is postulated that the high depth of cure of UDMA-based FC is much related to its high degree of monomer to polymer conversion, as previously discussed. Apart from the molecular structure and flexibility of monomers, Fujita et al 19 reported that the curing depth of resin composite strongly depended on the transmitted amount of visible light.…”
Section: Depth Of Curementioning
confidence: 88%